The Relationship Between Self-Efficacy and Aggressive Behavior in Boxers: The Mediating Role of Self-Control - Chen, Xin; Zhang, Guodong; Yin, Xueqin; Li, Yun; Cao, Guikang; Gutiérrez-García, Carlos; Guo, Liya (Frontiers in Psychology, 2019)
Aggressive behavior has been one of the core issues in sports psychology, whereas boxers’ aggressive behavior has received limited attention. Although some literature reported that self-efficacy is related to aggressive behavior, the mechanism whereby self-efficacy affects aggressive behavior remains unclear. The present study investigated the relationship between self-efficacy and aggressive behavior, as well as the effect of self-control as a mediating factor. This study uses the Self-efficacy Scale for Athletes, the Self-control Questionnaire for Athletes, and the Buss-Perry Aggression Questionnaire. This relationship is explored through self-reported measures from N= 414 Chinese professional boxers, n = 243 were male and n = 171 were female, the average age was M=17.72 years (SD = 3.147), the participants, the average number of years of exercise was M=3.89 years (SD = 2.734); Results showed that male boxers reported greater aggression than female boxers; It was found that the self-efficacy and self-control improved as age of the participants increased; The higher the level of competition, the higher levels of self-efficacy and self-control; Self-efficacy was negatively related with aggressive behavior and positively correlated with self-control. Self-control was also negatively correlated with aggressive behavior among boxers. Self-control had a full mediating effect on the relationship between self-efficacy and aggressive behavior.